Long term outcomes reporting the safety of breast conserving therapy compared to mastectomy: 20-year results of EORTC 10801 - Black, Dalliah M. (AME Publishing Company, 2013)
Large multicenter clinical trials have demonstrated the safety of breast conserving surgery and radiation (BCT) compared to modified radical mastectomy (MRM). At 20 years follow-up, the European Organization of Research and Treatment of Cancer (EORTC) 10801 trial reports the outcomes of distant metastasis (DM) and overall survival (OS) for stage 1 and 2 breast cancers treated from 1980-1986. Even though BCT had a higher 10 years local-regional recurrence (LRR) at 20% compared to MRM (12%), no significant difference was identified in long term OS (44% in the BCT group and 39% in the MRM group) or time to DM. Factors associated with increased LRR were dependent on biologic characteristics including larger tumor size, lymph node metastasis, and receptor subtype. BCT should be offered in appropriate patients when complete resection can be achieved. Continued research evaluating the heterogeneity of breast cancer subtypes will help further guide local-regional therapy for continued improvement in LRR, DM, and OS.